TEKNIK MENGENDALIKAN KEONG MAS PADA TANAMAN PADI (THE TECNICAL CONTROLLING OF GOLDEN SNAIL ON PLANT RICE) - Budiyono, Suharto (Jurnal Ilmu-Ilmu Pertanian, 2006)
Golden snail (Pomaceae canaliculata Lamarck) in area Yogyakarta on this time was not pest primer in plantating rice but golden snail need anticipation because golden snail potention to be pest primer. Golden snail growth, multiply fast and attack plant rice of fase vegetative. The controlling golden snail use approach to IPM (Integrade Pest Management) is the controlling pest bassid to aspec ecology and economic of management care of agroecosystem with combination many tecnic application. Succesful controlling of golden snail to plant rice was early, periodic,massive and continous.